ABOUT THE CHOICE OF PARAMETERS WHEN REPRESENTING THE NORMAL EARTH AS A REFERENCE FRAME IN GEODESY: ABOUT THE CHOICE OF PARAMETERS WHEN REPRESENTING THE NORMAL EARTH AS A REFERENCE FRAME IN GEODESY - Kirilova, Krasimira; Yanchev, Kiril (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
When using the Normal Earth as a reference frame, it is allowed to choose its parameters approximately, provided that there will be no difficulties in linearizing the boundary values. In many cases, however, it is convenient to find specific solutions corresponding to the selection of the Normal Earth parameters best suited to the real Earth. Thus, it is of interest to determine, as far as possible, the exact values of these parameters.